Discovery of Potential Plant-Based Anti-HCV Agents: Anti-Replicative Activity of Solanum surattense and Its Bioactive Flavonoids Against HCV-3a - Fareeda Islam,; Muhammad Nauman Ahsun,; Aeliya Batool, (Indus Journal of Bioscience Research, 2024)
Hepatitis C virus (HCV) infection remains a global health burden, with genotype 3a (HCV-3a) being highly prevalent in South Asia and associated with accelerated disease progression and reduced response to certain direct-acting antivirals (DAAs). Resistance-associated substitutions (RASs) continue to limit therapeutic efficacy, emphasizing the need for novel, cost-effective antiviral agents. In this study, we evaluated the anti-HCV potential of Solanum surattense leaves and flowers against HCV-3a replication in Huh-7 hepatoma cells. Methanolic extracts were prepared, and cytotoxicity was assessed via MTT assay, revealing cell viability >90% up to 105 µg/mL for both extracts. Huh-7 cells were transfected with full-length HCV-3a and NS3-expressing plasmids and treated with extracts at 52.5 and 105 µg/mL. Antiviral activity was quantified using qRT-PCR and NS3 protein expression analysis. Leaf extract demonstrated robust, dose-dependent inhibition of HCV-3a replication, achieving 65.1% and 88.2% inhibition at 52.5 µg/mL and 105 µg/mL, respectively, while flower extract exhibited moderate inhibition (42.7% and 57.9%). NS3 expression was similarly suppressed by leaf extract (61.4–85.7%). Notably, the antiviral efficacy of leaf extract at higher concentrations was comparable to daclatasvir (73.5% inhibition). These findings suggest that S. surattense leaves harbor bioactive flavonoids and related phytochemicals capable of targeting multiple stages of HCV replication without significant cytotoxicity.